Plasma brain-derived neurotrophic factor (pBDNF) and executive dysfunctions in patients with major depressive disorder. (9th August 2019) - Wagner, Stefanie; Kayser, Sarah; Engelmann, Jan; Schlicht, Konrad F.; Dreimüller, Nadine; Tüscher, Oliver; Müller-Dahlhaus, Florian; Braus, Dieter F.; Tadić, André; Neyazi, Alexandra; Frieling, Helge; Lieb, Klaus
Abstract: Objectives: Executive dysfunctions are frequently seen in patients with major depressive disorder (MDD) and normalise in many cases during effective antidepressant therapy. This study investigated whether a normalisation of executive dysfunctions during antidepressant treatment correlates with or can be predicted by clinical parameters or levels of brain-derived neurotrophic factor (BDNF). Methods: In 110 MDD patients with executive dysfunctions (percentile <16), executive functions and plasma BDNF levels were analysed at baseline, and days 14 and 56 of an antidepressant treatment. BDNF exon IV and P11 methylation status was studied at baseline. Results: Eighty patients (73%) experienced a normalisation of executive dysfunctions, while 30 (27%) suffered from persistent dysfunctions until day 56. Patients with persistent dysfunctions had significantly higher HAMD scores at days 14 and 56, and lower plasma BDNF levels at each time point than patients with a normalisation of dysfunctions ( F 1 = 10.18; P  = 0.002). This was seen for verbal fluency, but not processing speed. BDNF exon IV and p11 promoter methylation was not associated with test performance. Conclusions: Our results corroborate a concomitant amelioration of executive dysfunctions with successful antidepressant therapy and support a role of BDNF in the neural mechanisms underlying the normalisation of executive dysfunctions in MDD. ClinicalTrials.gov number: NCT00974155; EudraCT: 2008-008280-96